2014
DOI: 10.1080/17533015.2014.966313
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arts-in-medicine programming on the medical-surgical work environment

Abstract: Background: Arts in medicine programs have significant impacts on patients and staff in long-term care environments, but the literature lacks evidence of effectiveness on hospital units with shorter average lengths of stay. Methods: The qualitative study used individual structured interviews to assess the impacts of arts programming on job satisfaction, stress, unit culture, support, quality of care, and patient outcomes on a short-term medical-surgical unit, and used a qualitative cross comparison grounded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…The study highlights how the patient's sensory response is triggered or controlled by spatial elements, producing experience in viewing activities. Other studies affirm such argument, demonstrating how spatial elements can shape a patient's experience in space (Sonke et al, 2015;Belfiore, et al, 2015;Lankston, et al, 2010;Nanda et al, 2012;Cusack et al, 2010). Exploring openings that could be changed in size, the experiment requires children and adult respondents to put their hands through the openings.…”
Section: Seeing As a Transactionmentioning
confidence: 99%
“…The study highlights how the patient's sensory response is triggered or controlled by spatial elements, producing experience in viewing activities. Other studies affirm such argument, demonstrating how spatial elements can shape a patient's experience in space (Sonke et al, 2015;Belfiore, et al, 2015;Lankston, et al, 2010;Nanda et al, 2012;Cusack et al, 2010). Exploring openings that could be changed in size, the experiment requires children and adult respondents to put their hands through the openings.…”
Section: Seeing As a Transactionmentioning
confidence: 99%
“…However, there is evidence that arts in health programmes can improve clinical outcomes for patients such as reducing stress, anxiety, pain and fatigue from medical or surgical interventions, and shortening the length of hospital stay (Putland, ; Staricoff & Clift, ; Stuckey, ). Arts‐based approaches can result in patients experiencing increased sense of control, increased self‐awareness and sense of self, reduced isolation and fear, and overall improved mental, emotional and spiritual well‐being (Baumann, Peck, Collins, & Eades, ; Sonke et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Benefits for nurses in settings where arts programmes are in place include increased engagement and well‐being, decreased stress and improved nurse‐patient communication and relations. Nurses can also experience increased satisfaction with care provision when they see the benefits for patients (Sonke et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arts programs in clinical environments have proven beneficial to patient outcomes and staff experiences (Sonke et al, 2015). An interesting correlation elucidated by Sonke and colleagues indicated that the presence of an arts program affected the nursing unit culture, which affected the nursing practice, which affected the quality of care.…”
Section: Elevator Musicmentioning
confidence: 99%